2020
DOI: 10.5539/ijel.v10n3p92
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneity of Speech Errors: A Diagnostic Psycholinguistic Case Study

Abstract: The aim of this study is to use speech errors as a verbal means of communication to clarify the psychological aspects of George W. Bush’s character. Bush’s character is chosen for being highly controversial, having received the lowest approval rating in 2008 and the highest approval rating after the September 11 attacks. To achieve the aim of this study, a psycholinguistic approach is adopted in addition to a speech production model set by Dell (1999), and Chang and Griffin (1999). Some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…The closeness rates can be attributed to the Egyptian researchers' keen desire to represent and emphasize their stances in every situation. This finding goes in harmony with Abdi (2002), Cao (2014), Abdulaal and Abuslema (2020), and Abdollahzadeh (2011) who pointed out that academic articles fall down if their authors do not show clearly their emphatic stances in every single situation. In the Saudi discussion sections, on the other hand, boosters, code glosses, engagement, frame markers, and transitions have reported far rates from the N-level; whereas only attitudes and hedges were much close to the native normal level.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The closeness rates can be attributed to the Egyptian researchers' keen desire to represent and emphasize their stances in every situation. This finding goes in harmony with Abdi (2002), Cao (2014), Abdulaal and Abuslema (2020), and Abdollahzadeh (2011) who pointed out that academic articles fall down if their authors do not show clearly their emphatic stances in every single situation. In the Saudi discussion sections, on the other hand, boosters, code glosses, engagement, frame markers, and transitions have reported far rates from the N-level; whereas only attitudes and hedges were much close to the native normal level.…”
Section: Discussionsupporting
confidence: 71%
“…A general overview of the previous studies on metadiscourse resources showed that metadiscoursal devices varied across different text types such as newspapers (Abdulaal, M., 2020;Yeganeh, Heravi, & Sawari, 2015;Dafouz-Milne, 2008), textbooks (Hyland, 1999;, research articles (Dahl, 2004;Kim & Lim, 2013), academic essays (Hyland, 2007;Adel, 2012;Bruce, 2010), argumentative essays (Anwardeen, Luyee, Gabriel, & Kalajahi, 2013) and theses/dissertations (Hyland, 2010) generated by native and non-native writers of English. Although these research studies focused mostly on the overall frequency of metadiscourse devices, they clearly ignored the functional analysis of the resources.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In addition to other relevant benefits, mastering grammatical rules helps learners avoid language fossilization and improves their execution. Furthermore, understanding the fundamentals of language structure helps learners become independent thinkers who can manage their learning process even when they are not in school or when there is a time limit on the use of classroom knowledge (Abdulaal & Abuslema, 2020).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…They go on to say that teaching reading strategies and fostering autonomous readers who can really access all types of materials by themselves is the most beneficial service teachers can offer to their EFL learners (M. A. Abdulaal & Abuslema, 2020).…”
Section: Introductionmentioning
confidence: 99%